In Vivo Predictors of Renal Cyst Pseudoenhancement at 120 kVp - Patel, Jeet (AJR Am J Roentgenol, 2014)
OBJECTIVE: The purpose of this article is to assess the effects of various CT, patient, and renal cyst characteristics on the occurrence of pseudoenhancement in in vivo renal mass CT examinations using subtraction MRI as the reference standard. MATERIALS AND METHODS: Adult patients imaged with 120-kVp standard kernel biphasic renal mass protocol CT and dynamic contrast-enhanced MRI of the abdomen from January 1, 2005, through May 4, 2012, were identified. Those with nonenhancing Bosniak categories I and II cysts on MRI were selected (n = 33 patients; 110 cysts). By treating measured cyst enhancement (nephrographic CT attenuation minus unenhanced CT attenuation) as either a continuous or categoric outcome variable, a variety of CT, patient-level, and renal cyst characteristics were assessed using mixed effect multivariate models. RESULTS: On univariate assessment, cysts that exhibited pseudoenhancement (> 10 HU) were significantly more endophytic (p = 0.02), significantly smaller (p = 0.0004), and adjacent to significantly higher attenuation renal parenchyma in the nephrographic phase (p = 0.02). On multivariate assessment, cyst diameter (p < 0.0001) and background nephrographic phase parenchymal attenuation (p = 0.003) were the strongest in vivo predictors of pseudoenhancement. The odds of pseudoenhancement occurring increased by 2.14 (95% CI, 1.41–3.23) for every 5-mm decrease in renal cyst diameter and increased by 2.45 (95% CI, 1.41–4.26) for every 25-HU increase in enhanced renal parenchymal attenuation. Endophytic growth was not significant in the multivariate analyses (p = 0.07). CONCLUSION: Renal cyst size and enhanced renal parenchymal attenuation are better in vivo predictors of pseudoenhancement than is endophytic growth pattern.